Identification and functional analysis of inhibitor of NF-κB kinase (IKK) from Scylla paramamosain: The first evidence of three IKKs in crab species and their expression profiles under biotic and abiotic stresses. (July 2018) - Jiang, Mei; Tu, Dan-Dan; Gu, Wen-Bin; Zhou, Yi-Lian; Zhu, Qi-Hui; Guo, Xiao-Ling; Shu, Miao-An
Abstract: IKK (inhibitor of NF-κB kinase) is the critical regulator for NF-κB (nuclear factor-κB) pathway against pathogenic invasion in vertebrates or invertebrates. However, the IKK from crab species has not yet been identified. In the present study, three full-length cDNA sequences of IKK s from mud crab Scylla paramamosain, designated as SpIKKβ, SpIKKε1 and SpIKKε2, were firstly cloned through RT-PCR and RACE methods. This is also the first report about the identification of two IKKε genes in mud crab and even in crustaceans. The SpIKKβ cDNA was 2824 bp in length with an open reading frame (ORF) of 2382 bp, which encoded a putative protein of 793 amino acids (aa). The ORF of two SpIKKε isoforms, SpIKKε1 and SpIKKε2, were 2400 bp and 2331 bp in length encoding 799 aa and 776 aa, respectively. The crucial conserved residues and functional domains, including the kinase domains (KDs) and leucine zipper (LZ), were identified in all Sp IKKs. Phylogenetic analysis suggested that Sp IKKβ was classified into the IKKs class while Sp IKKεs could be grouped into the IKK-related kinases class. The qRT-PCR analysis showed that three SpIKK s were constitutively expressed in all tested tissues and the highest expression levels of SpIKKβ and SpIKKε s were all in hemocyte. The gene expression profiles of SpIKK s were distinct when crabs suffered biotic and abiotic stresses including the exposures of Vibrio alginolyticus, poly (I:C), cadmium and air exposure, suggesting that the SpIKK s might play different roles in response to pathogens infections, heavy metal and air exposure. Moreover, IKKs from mud crab can significantly activate mammalian NF-κB pathway, suggesting the function of IKKs might be evolutionally well-conserved. Results of the RNAi experiments suggested that Sp IKKs might regulate the immune signaling pathway when hemocytes were challenged with V. parahemolyticus or virus-analog poly (I:C). All of these results indicated that the obtained Sp IKKs might be involved in stress responses against biotic or abiotic stresses, and it also highlighted their functional conservation in the innate immune system from crustaceans to mammals. Highlights: Three IKK genes were firstly identified from the crab species. Function of IKKs in activating NF-κB pathway may be evolutionally conserved. Expression profiles of IKKs under both biotic and abiotic stresses were firstly investigated in arthropods.